Characteristics and Outcomes of Intravenous Thrombolysis in Mild Ischemic Stroke Patients - Tang, Huan; Yan, Shenqiang; Wu, Chenglong; Zhang, Yanxing (Frontiers in Neurology, 2021)
Objective: This study assessed the characteristics of intravenous thrombolysis (IVT) on early neurological deterioration (END) and functional outcome in mild ischemic stroke patients. Methods: Data were obtained from acute mild ischemic stroke patients (defined as having a National Institute of Health Stroke Score (NIHSS) ≤5) treated with IVT in our hospital from July 2017 to December 2020. END was defined as the NIHSS increased ≥1 over the baseline at 24h after IVT. A modified Rankin Scale (mRS) ≤1 at three months was considered as a favorable outcome, and a mRS ≥2 at three months was an unfavorable outcome. Results: Two hundred thirty-three acute mild ischemic stroke patients (all patients underwent MRI imaging and DWI restriction) with IVT were included in this study. Thirty-one patients experienced END, and fifty-seven patients experienced an unfavorable outcome at three months. Using multivariate analysis, END was associated with an elevated baseline systolic blood pressure (SBP) (OR=1.324, 95% CI, 1.053-1.664, P=0.016) and coronary heart disease (OR=4.933, 95% CI, 1.249-19.482, P=0.023). An unfavorable outcome at three months after IVT was associated with a baseline elevated SBP (OR=1.213, 95% CI, 1.005-1.465, P=0.045), baseline NIHSS (OR=1.515, 95% CI, 1.186-1.935, P=0.001), prior hyperlipemia (OR=3.065, 95% CI, 1.107-8.482, P=0.031), cardioembolic stroke (OR=0.323, 95% CI, 0.120-0.871, P=0.025), and END at 24h (OR=4.531, 95% CI, 1.950-10.533, P＜0.001) in mild ischemic stroke patients. Conclusion: In mild ischemic stroke patients with IVT, an elevated baseline SBP and coronary heart disease were associated with END. The elevated baseline SBP, baseline NIHSS, a history of prior hyperlipemia, cardioembolic stroke and END at 24h after IVT were useful in predicting an unfavorable outcome at three months.